The complete mitochondrial genome of Psolodesmus mandarinus McLachlan, 1870 (Odonata: Calopterygidae). Issue 1 (2nd January 2019) - Wang, Liang-Jong; Lin, Min-Ying; Shiao, Shiuh-Feng; Sung, Chia-Hsuan
Abstract: In the present report, we describe the complete mitochondrial genome of Psolodesmus mandarinus, from the Hualien County, Taiwan. This mitogenome is 15, 176 bp long, containing 13 protein-coding, 22 tRNA, and two rDNA genes. Nucleotide composition of the whole mitogenome was 41% for A, 25.92% for T, 19.06% for C, and 14.03% for G. The AT and GC skewness of mitogenome sequence was 0.225 and 0.152, showing the A-skew and C-skew. The reconstructed phylogenetic relationships of 23 Odonata species based on 13 protein-coding genes were highly supported. P. mandarinus grouped within the clade including the other three Calopterygidae genera, Mnais, Vestalis, and Atrocalopteryx was solid supported (100%). It was relatively close to Mnais costalis in the phylogenetic analysis. Our study will be useful for the population genetics, biogeography, and conservation of P. mandarinus in the future.